The utilisation of whole exome sequencing to dissect the genetic aetiology of familial Parkinson’s disease in a South African Afrikaner family - Sebate, Boiketlo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.